2006
DOI: 10.1097/01.ico.0000160970.58330.09
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Epithelial Viability on Stromal Keratocyte Apoptosis in Porcine Corneas Stored in Optisol-GS

Abstract: Stromal keratocytes underwent apoptosis in Optisol-GS. The absence of corneal epithelium during preservation further increased the stromal keratocyte apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
7
1
Order By: Relevance
“…Optisol GS™ is a common preservative medium used for corneal tissues, and has been shown to be particularly suitable for preservation of the corneal endothelium in hypothermia36; however, some reports have suggested that the medium is not suitable for the preservation of corneal epithelium3738. The results of our experiment clearly showed that Optisol GS™ is not suitable for preservation of the corneal epithelium or its stem cells.…”
Section: Discussioncontrasting
confidence: 53%
“…Optisol GS™ is a common preservative medium used for corneal tissues, and has been shown to be particularly suitable for preservation of the corneal endothelium in hypothermia36; however, some reports have suggested that the medium is not suitable for the preservation of corneal epithelium3738. The results of our experiment clearly showed that Optisol GS™ is not suitable for preservation of the corneal epithelium or its stem cells.…”
Section: Discussioncontrasting
confidence: 53%
“…However, some reports have suggested that the use of Optisol-GS is not suitable for the preservation of corneal epithelium 8,9 . In contrast, there are other solutions that have been shown to be an effective compound for the preservation of human corneal epithelium 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CSK preservation in Optisol-GS was reported to be suboptimal. The cells underwent apoptosis, which was more significant after 5 days of storage in Optisol-GS (2). Debridement of corneal epithelium during storage further boosted CSK apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were seeded at 10 4 cells per cm 2 on collagen I-coated culture wells (BD Biosciences, Franklin Lakes, NJ, USA). To propagate genuine CSKs, our results must meet three basic requirements: (1) maintenance of cells with dendritic morphology, (2) lack of fibroblast features (negative expression of αSMA and F-actin stress fiber pattern), and (3) expression of CSK markers (ALDH1A1, ALDH3A1, lumican, keratocan, and COL8A2). We cultured the cells with various chemicals and growth factors, including soluble amnion stromal extract (ASE; preparation details as shown below), ROCK inhibitor Y27632 (10 mM; Millipore, Billerica, MA, USA), insulin-like growth factor 1 (IGF1; 10 ng/ml; Invitrogen), and/or fetal bovine serum (FBS; Invitrogen).…”
Section: Methodsmentioning
confidence: 99%